Intramolecular Oxidative Diaryl Coupling of Tetrasubstituted Diphenylamines for the Preparation of Bis(trifluoromethyl) Dimethyl Carbazoles - Duda, Addison M.; Giurini, Michael T.; Gillmore, Jason G.; Guarr, Thomas F. (SynOpen, 2021)
Synthetic preparation of carbazoles can be challenging, requiring ring-building strategies and/or precious metal catalysts. Presented herein is a method for the preparation of carbazoles with the use of inexpensive and reliable hypervalent iodine chemistry. An oxidative single-electron-transfer (SET) event initiates cyclization for the preparation of our trifluoromethyl carbazoles. This method has been shown to be useful for a variety of bis(trifluoromethyl)carbazole isomers that are of primary interest for use as battery materials.
Keywords: intramolecular coupling; metal-free; electron-deficient carbazoles; hypervalent iodine